Studi Literature Riview: Kesulitan Belajar Mahasiswa Pendidikan Matematika - Mustika Nurbayeni; Rusi Ulfa Hasanah; Zulayli Syahrani (International Forum of Researchers and Lecturers, 2024)
This research aims to clarify the causes of students' learning difficulties which are an important concern in the development of mathematics education. Learning difficulties are influenced by various internal and external factors, including individual abilities and the learning environment. The method used in this research is the bibliometric method. Data collection was carried out by documenting all papers that contained research findings similar to this research report. The results of this research show that students' mathematics learning difficulties are a complex and serious problem.